1995
DOI: 10.1523/jneurosci.15-05-04102.1995
|View full text |Cite
|
Sign up to set email alerts
|

Amphetamine redistributes dopamine from synaptic vesicles to the cytosol and promotes reverse transport

Abstract: Whether amphetamine acts principally at the plasma membrane or at synaptic vesicles is controversial. We find that d-amphetamine injection into the Planorbis giant dopamine neuron causes robust dopamine release, demonstrating that specific amphetamine uptake is not required. Arguing for action at vesicles, whole-cell capillary electrophoresis of single Planorbis dopamine neurons shows that amphetamine reduces vesicular dopamine, while amphetamine reduces quantal dopamine release from PC12 cells by > 50% per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
456
3
1

Year Published

1997
1997
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 581 publications
(475 citation statements)
references
References 36 publications
15
456
3
1
Order By: Relevance
“…Clinical imaging studies have also found significant deficits in dopaminergic function among chronic MA users, including reductions in DAT density (Volkow et al, 2001b) and DA receptor occupancy (Volkow et al, 2001a;Volkow et al, 2001c), which are thought to contribute to the dysphoric symptoms that accompany MA dependence and withdrawal. Chronic highdose MA exposure is thought to produce these neurotoxic effects by impairing the ability of synaptic vesicles to take up DA via disruption of the vesicular proton gradient necessary for VMAT-2 functioning (Sulzer et al, 1995;Sulzer and Rayport, 1990), resulting in accumulation of cytoplasmic DA and the subsequent production of harmful reactive oxygen species (Cubells et al, 1994;Fleckenstein et al, 1997). DA reuptake blockers such as bupropion increase vesicular dopamine uptake via enhancement of VMAT-2 function (Brown et al, 2001;Rau et al, 2005) suggesting that treatment with bupropion may counteract the MA-induced accumulation of cytosolic DA and reactive oxygen species thereby reducing the neurotoxic effects of MA.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical imaging studies have also found significant deficits in dopaminergic function among chronic MA users, including reductions in DAT density (Volkow et al, 2001b) and DA receptor occupancy (Volkow et al, 2001a;Volkow et al, 2001c), which are thought to contribute to the dysphoric symptoms that accompany MA dependence and withdrawal. Chronic highdose MA exposure is thought to produce these neurotoxic effects by impairing the ability of synaptic vesicles to take up DA via disruption of the vesicular proton gradient necessary for VMAT-2 functioning (Sulzer et al, 1995;Sulzer and Rayport, 1990), resulting in accumulation of cytoplasmic DA and the subsequent production of harmful reactive oxygen species (Cubells et al, 1994;Fleckenstein et al, 1997). DA reuptake blockers such as bupropion increase vesicular dopamine uptake via enhancement of VMAT-2 function (Brown et al, 2001;Rau et al, 2005) suggesting that treatment with bupropion may counteract the MA-induced accumulation of cytosolic DA and reactive oxygen species thereby reducing the neurotoxic effects of MA.…”
Section: Discussionmentioning
confidence: 99%
“…This leads to an increase in the intracellular binding sites of DAT for dopamine, resulting in the exchange of extracellular amphetamine by intracellular dopamine, and leading to an increase in extracellular dopamine [289]. When present in higher extracellular concentrations, amphetamine may diffuse into the cell, due to its lipophilicity [290,291]. Amphetamine also interferes with VMATͲ2 function, impairing the active transport of the monoamines into synaptic vesicles, where they are stored.…”
Section: Amphetaminesdopamine and Pdmentioning
confidence: 99%
“…At low concentrations, amphetamine is transported by the DAT to the cytosol and increases the intracellular binding sites of the DAT for dopamine, resulting in the exchange of extracellular amphetamine by intracellular dopamine, and leading to an increase in extracellular dopamine (Jones et al, 1999). When present at higher extracellular concentrations, amphetamine may diffuse into the cell, due to its lipophilicity (Sulzer et al, 1995;Kahlig et al, 2005).…”
Section: Short-term Neurochemical Effectsmentioning
confidence: 99%